2022
DOI: 10.33549/physiolres.934717
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of α2-Adrenergic Receptors in the Caudal Raphe Region Enhances the Renal Sympathetic Nerve Activity Response to Acute Intermittent Hypercapnia in Rats

Abstract: The study investigated the role of α2-adrenergic receptors of the caudal raphe region in the sympathetic and cardiovascular responses to the acute intermittent hypercapnia (AIHc). Urethane-anesthetized, vagotomized, mechanically ventilated Sprague-Dawley rats (n=38) were exposed to the AIHc protocol (5×3 min, 15 % CO2+50 % O2) in hyperoxic background (50 % O2). α2-adrenergic receptor antagonist-yohimbine was applied intravenously (1 mg/kg, n=9) or microinjected into the caudal raphe region (2 mM, n=12) prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…On the contrary, urethane does not seem to have a specific and predominant target for exerting its action and is preferentially used in experiments where the preservation of the reflexes is essential, as the observations closely mirror those made in conscious animals [53][54][55][56][57]. Previous reports indicate that both PNA and RSNA responses to chemoreflex activation may depend not only on the strength and type of the intermittent stimulus but also on the reoxygenation pattern [41,[58][59][60]. It has been demonstrated that hyperoxia has minimal effects on the magnitude of PNA response but can significantly attenuate the sympathetic response to acute airway obstruction in rats [59].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…On the contrary, urethane does not seem to have a specific and predominant target for exerting its action and is preferentially used in experiments where the preservation of the reflexes is essential, as the observations closely mirror those made in conscious animals [53][54][55][56][57]. Previous reports indicate that both PNA and RSNA responses to chemoreflex activation may depend not only on the strength and type of the intermittent stimulus but also on the reoxygenation pattern [41,[58][59][60]. It has been demonstrated that hyperoxia has minimal effects on the magnitude of PNA response but can significantly attenuate the sympathetic response to acute airway obstruction in rats [59].…”
Section: Discussionmentioning
confidence: 82%
“…Next, the animals were placed in a prone position and fixed in a stereotaxic frame (Lab Standard; Stoelting Co., Wood Dale, IL, USA). A dorsal approach at the level of C5 nerve rootlet was used to access the right phrenic nerve, and the retroperitoneal approach was used to access the left renal sympathetic nerve, as previously described [23,41]. Each intact nerve was mounted on a silver wire electrode and covered with silicone gel to prevent it from drying and minimize noise artefacts.…”
Section: General Proceduresmentioning
confidence: 99%